POTENSI SUMBER DAYA SEBAGAI UPAYA PEMBERDAYAAN PEREMPUAN DI PONOROGO (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2017)
This study aims to determine the factors that cause unemployment of women in Ponorogo, how the development of entrepreneurship and empowerment of women areand the obstacles faced. This research was located in Ponorogo Regency, East Java, which has the potential of entrepreneurship in the field of processing bothe yam into a snack of bothe chips. The number of unemployed women is a potential that is biased optimized for the development of bothe chips business. This research uses quantitative method supported by qualitative method. The research instrument used is questionnaire as direct interview guide. The results show that many women in rural areas are unemployed because of their low educational background and inadequate skills. The potential of a very large crop of bothe yam is still not maximized and has not been utilized to be a profitable economic source. As a result, there is a lot of poverty and unemployment in this area. The absence of parties who provide soft skills to cultivate bothe yam makes the women skills development in this area becomes so slow